Prognostic Value of the CHADS2 Score for Adverse Cardiovascular Events in Coronary Artery Disease Patients Without Atrial Fibrillation—A Multi‐Center Observational Cohort Study. Issue 8 (16th August 2017) - Tabata, Noriaki; Yamamoto, Eiichiro; Hokimoto, Seiji; Yamashita, Takayoshi; Sueta, Daisuke; Takashio, Seiji; Arima, Yuichiro; Izumiya, Yasuhiro; Kojima, Sunao; Kaikita, Koichi; Matsui, Kunihiko; Fujimoto, Kazuteru; et al.
Abstract : Background: The CHADS2 score has mainly been used to predict the likelihood of cerebrovascular accidents in patients with atrial fibrillation. However, increasing attention is being paid to this scoring system for risk stratification of patients with coronary artery disease. We investigated the value of the CHADS2 score in predicting cardiovascular/cerebrovascular events in coronary artery disease patients without atrial fibrillation. Methods and Results: This was a multicenter, observational cohort study. The subjects had been admitted to one of the participating institutions with coronary artery disease requiring percutaneous coronary intervention. We calculated the CHADS2 scores for 7082 patients (mean age, 69.7 years; males, 71.9%) without clinical evidence of atrial fibrillation. Subjects were subdivided into low‐ (0–1), intermediate‐ (2–3), and high‐score (4–6) groups and followed for 1 year. The end point was a composite of cardiovascular/cerebrovascular death, nonfatal myocardial infarction, and ischemic stroke at 1‐year follow‐up. Rates of triple‐vessel/left main trunk disease correlated positively with CHADS2 score categories. CHADS2 scores among single, double, and triple‐vessel/left main trunk groups were 2 (1–2), 2 (1–3), and 2 (2–3), respectively ( P <0.001). A total of 194 patients (2.8%) had a cardiovascular/cerebrovascular event, and Kaplan–Meier analysis demonstrated a significantly higher probability of cardiovascular/cerebrovascular events in proportion to a higher CHADS2 score (log‐rank test, P <0.001). Multivariate Cox hazard analysis identified CHADS2 score (per 1 point) as an independent predictor of cardiovascular/cerebrovascular events (hazard ratio, 1.31; 95% CI, 1.17–1.47; P <0.001). Conclusions: This large cohort study indicated that the CHADS2 score is useful for the prediction of cardiovascular/cerebrovascular events in coronary artery disease patients without atrial fibrillation.